Pemanfaatan Daun Pisang Kering (Klaras) sebagai Pewarna Alami Jajanan Tradisional Ongol-Ongol - Nindhita, Vidya; Putri, Nilawati Yan; Alfirda, Rodiyatan; Hamdani, Rakha Agil; Harianto, Mohammad Yasin (Yayasan Arrahman Nahdlatul Wathan, 2024)
The utilisation of dried banana leaves (klaras) as a natural food colouring used to make traditional Ongol-Ongol snacks was carried out considering the large amount of dried banana leaves that end up as waste. This activity is useful to help improve the economy of the surrounding community by providing business opportunities and additional income, introducing and promoting the snacks made, the community can develop local culinary potential and increase the competitiveness of their products. Ongol-Ongol production can also provide education and training to the community in snack making, including cooking techniques, small business management, and knowledge of the raw materials used. Through this education and training, the community can also improve their skills and knowledge in culinary and food business. This training was attended by the community of Taman Sare Village. The methods used were counselling and hands-on training. The result of this training is that the people of Taman Sare Village can make Ongol-Ongol traditional snacks from dried banana leaves (klaras) which can be used in the natural colouring of these snacks and increase the knowledge and insight of the people of Taman Sare Village, Dungkek District, Sumenep Regency.